NuSTAR Detection of an Absorption Feature in ESP 39607: Evidence for an Ultrafast Inflow? - Alessandro Peca; Michael J. Koss; Roberto Serafinelli; Claudio Ricci; C. Megan Urry; Giulia Cerini; Peter G. Boorman (The Astrophysical Journal)
We report the serendipitous discovery of an absorption feature at 4.8 keV in the NuSTAR spectra of ESP 39607, a Seyfert 2 galaxy at z = 0.201, observed in 2023 May and 2024 August. The feature is detected in both observations with individual significance levels between 2 σ and 3 σ , computed with multiple statistical methods. The combined probability of detecting it in both observations is ≳4 σ . The absorption feature is consistent with an ultrafast inflow (UFI) potentially associated with Fe xxv or Fe xxvi K α transitions. The inferred inflow velocity is ∼0.15–0.20 c , with an estimated launching radius of 22–89 R _g , depending on the assumed iron transition and whether radiation pressure is accounted for. Photoionization modeling associates the UFI primarily with Fe xxv K α absorption, blended with a minor contribution from Fe xxvi K α . Alternative explanations, including associations with the warm-hot intergalactic medium or outflows of lighter elements, are investigated but found unlikely. If confirmed, this detection represents a rare example of a UFI, providing valuable evidence into extreme and/or nonstandard accretion processes near supermassive black holes. Follow-up observations with higher-resolution X-ray spectroscopy, such as with XMM-Newton or XRISM, will be essential to confirm the nature of this feature and better constrain the physical mechanisms driving it.